2016
DOI: 10.1016/j.nedt.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of teaching methods used to develop critical thinking in nursing and midwifery undergraduate students: A systematic review of the literature

Abstract: Whilst this review aimed to identify effective teaching strategies that promote and develop critical thinking, flaws in methodology and outcome measures contributed to inconsistent findings. The continued use of generalised CT tools is unlikely to help identify appropriate teaching methods that will improve CT abilities of midwifery and nursing students and prepare them for practise. The review was limited to empirical studies published in English that used measures of critical thinking with midwifery and nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 40 publications
7
67
0
12
Order By: Relevance
“…These conceptions are similar to what is described in the national and international nursing literature. 5,15,20,21 In a more general concept, in the various areas of knowledge beyond health, such as psychology, philosophy, education, the critical thinker has been reported as an individual who analyzes, judges in an intentional, reflective manner and who always seeks truth impartially and weighted values. 5,7 In nursing, it has been defined as someone with the capacity to employ the highest cognitive abilities to analyze, question, evaluate, conceptualize and understand clinical problems in a more precise, logical and adequate way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These conceptions are similar to what is described in the national and international nursing literature. 5,15,20,21 In a more general concept, in the various areas of knowledge beyond health, such as psychology, philosophy, education, the critical thinker has been reported as an individual who analyzes, judges in an intentional, reflective manner and who always seeks truth impartially and weighted values. 5,7 In nursing, it has been defined as someone with the capacity to employ the highest cognitive abilities to analyze, question, evaluate, conceptualize and understand clinical problems in a more precise, logical and adequate way.…”
Section: Discussionmentioning
confidence: 99%
“…As the present study attempts to do, conducting research comparing teaching methods or methodologies appears to be suitable, which considers CT as a superior mental function achieved within a Zone of Proximal Development (ZPD) or a stimulus to a conscious behavior of the student, as proposed by Vygotsky's Historical-Cultural Theory. [11][12][13][14][15][16] As an indispensable tool for care practice, CT should not be confused with innate capacity, but understood as an ability that can be taught and learned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that some strategies have a better performance in the promotion of CT among undergraduate Nursing students, such as Problem Based Learning (PBL), Simulation, Concept Mapping, reflection and the association between two or more strategies (8)(9) .…”
Section: Influence Of Communicative Action Theory On Critical Thinkinmentioning
confidence: 99%
“…In this way, understanding the classroom as an environment for CT promotion is essential in nursing education, as well as understanding the nurse as an educator who is a responsible and ethical professional, creating an environment conducive to learning in which the aim is to train competent, effective and autonomous nurses (8)(9) . Nursing educators should provide a captivating and interesting teaching and learning process in Nursing programs that focus on the development of these ideals.…”
Section: Influence Of Communicative Action Theory On Critical Thinkinmentioning
confidence: 99%